Diseño de un modelo de agroecosistema sostenible agroecológico en la parroquia Orianga, cantón Paltas, Provincia de Loja - Cando Condoy, Luis Miguel (2015)
This research was conducted in the parish Orianga, farm "Secrets of grandparents" of the Condoy family - Yanangómez to establish a model Agoecosystem, which recognizes that knowledge and understanding of the natural environment and social, can guide the producer to make a more successful intervention in the management of agro-ecosystems and natural resources, thus promoting local development. Five altitudes ranging from 789-970 m were established. The study of mesofauna, flora and fauna, was performed to determine the number of individuals, species, genera and families according to extract each altitude level; recorded 770 trees, 304 shrubs, 828 epiphyte, 125 lianas, grasses 1184, 786 individuals and 32 mesofauna soil fauna throughout the agroecosystem. The floor of the property has a clay texture with effective depth of 30 cm, with slopes of between 43 and 65 % of Class IV, according Iñiguez (1999), with a pH of 5.38 and is at an average level of MO as 3.36 %. It has two creeks and the kind of water circulating in the Quebrada S/N is C1S1 Water low salinity and low sodium content. The agricultural production of the estate, the 61.59 % is intended for sale and 38.41 % for consumption. With the results obtained during agroecosystem design was developed, taking into account all the potential that owns the farm to make better use of the production units, which generate a space for family Condoy - Yanangómez in which there is an interaction between all components (soil, air, water, energy, living and technologies) with proper management of natural resources, being the center and engine of the estate. The model proposed ventures in agro-ecosystem: stingless bees, beekeeping, organic fertilizers, agroforestry nursery, semi-evergreen and perennial crops, forest protection by adding 1, 2 and 3, readjustment of housing and the installation of a discharge area, washing, sorting , packaging, storage and toilets. Whereas for them an analysis of social, environmental and economic sustainability that contributes significantly to the improvement of the farm.